Outcomes of a quality improvement project aimed at improving delivery of new anticancer drug education to nursing in an academic-community hybrid model. Issue 28 (1st October 2022) - Blouin, Gayle C.; Derosier, Crystal; Man, Yun; Morris, Amy; Roberts, Daniel Aaron
Abstract : 50 Background: Educating staff on new anticancer medications is imperative for patient safety. Infusion nurses at Dana Farber Cancer Institute (DFCI) satellite infusion centers were surveyed on their comfort level administering newer oncology drugs. Results revealed only 57% of nurses were "extremely comfortable or somewhat comfortable, " while 32% of nurses were "somewhat uncomfortable or very uncomfortable." This project aimed to increase percentage of nurses at the satellites indicating they are "extremely comfortable" or "somewhat comfortable" from baseline of 57% to ≥75%. Methods: An interdisciplinary team including pharmacy, medical oncology, and nursing was formed to analyze workflows around new drug onboarding, staff education, and satellite communication. The team utilized Plan-Do-Study-Act (PDSA) cycle methodology. Tools included process maps and fishbone to identify areas of improvement. Intervention development tools included a Pareto chart and a priority matrix. Results were analyzed using statistical process control charts. Results: PDSA cycle 1 consisted of making the pharmacy driven education sheet, At-A-Glance (AAG), more accessible for new drugs. AAGs for drugs approved by the FDA in the previous 18 months were posted on the DFCI pharmacy intranet page. Nurses were educated on how to access AAG weekly. For PDSA cycle 2, the survey was modified to target individual nurses administering new drugs rather than all nurses. A "Nursing consideration" section was added to the AAG template and workflow developed; Navigation and review of AAG was added to nursing competency. Monthly nursing/pharmacy huddles were established to optimize communication. These interventions increased the percentage of nurses indicating they are "extremely comfortable" or "somewhat comfortable" to ≥75% which was sustainable through PDSA cycle 2 (see Table). Conclusions: Making an easy-to-use nursing education resource accessible improved nursing comfort level. There were challenges with nursing survey due to COVID-19 surge and staff shortages. Routine huddles are essential for sustainability.Survey Dates Nursing comfort level: extremely comfortable or somewhat comfortable September, 2021 57% November, 2021 80% December, 2021 100% January, 2022 82% February, 2022 82%